Meningkatkan Kemampuan Kolase Melalui Penerapan Metode Demonstrasi Dengan Media Kapas Kelompok B TK ABA XVIII Tambak (JURNAL ILMIAH TUT WURI HANDAYANI, 2025)
The problem of this research is the low ability of collage using cotton media. This research is to improve collage creativity in group B children at ABA XVIII Tambak Kindergarte, the research sample is 12 children. The data collection technique uses observation techniques and the research instrument uses is an observation sheet. The benefits obtained from this learning method are the student feel happy to be able to produce collage art easily. From learning collage using cotton media, it can make students more creative. The action applied is the step demonstration method in making collages using cotton media, starting from taking and sticking cotton to forming simple images. Data was collected through observation sheets. The results of the study showed a significant increase in children’s collage abilities after the demonstration method was applied with cotton media. The application of the demonstration method helps children understand the steps for making collage clearly, while cotton media provides an interesting and safe texture experience for children. Thus, it can be concluded that the application of the demonstration method with catton media is effective in improving the collage abilities of earlie childood children group B. This study recommends that teachers can use demonstration methods with variations of other media to develop childrens art abilities more optimally.